Brief Physical-Mechanical Characterization of Wood from Maranhão for the Manufacture of Xylophone Bars - Guilhon, David [UNESP]; de Jesus Costa Leite Bezerra, Helton; Lourenço, Anna Karen Lima; Pinheiro, Olímpio Jose [UNESP] (Springer Nature, 2023)
This paper presents a comparative analysis between the woods generally used for the manufacture of xylophone bars and those normally sold and native to Maranhão, in which the physical and mechanical properties were presented. Thus, 23 native woods were selected to verify their properties in comparison with the 16 traditional species, selected with the help of 5 graphs focused on the shrinkage coefficient, modulus of rupture and Janka hardness, for comparison and based on Wegst and other authors. 12 native woods suitable for the manufacture of the xylophone, 5 of which were selected for the professional modality of the instrument, which are: Sucupira, Jatobá, Cumaru, Maçaranduba and Pau-d'arco, and 8 for the educational modality, namely: Bacuri, Goiabão, Maracatiara, Piqui, Piquiá, Copaíba, Cerejeira and Louro-rosa. The other woods were considered unsuitable for this purpose due to their properties below the observed spectra.
Keywords: Musical instruments; Native woods; Product design; Xylophone